AGAINST MORALIZED SECULARISM - RUDAS, SEBASTIÁN (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2017)
Moralized secularism is the view that “secularism” is defined in relation to certain moral values. Jocelyn Maclure and Charles Taylor’s “liberal pluralism” is an influential version of moralized secularism, for it states that freedom of conscience and equal respect are the fundamental moral values of secularism. I present the objection that secularism is a redundant category because it carries no distinctive normative content that cannot be found in the more general, and less divisive, terminology of liberalism and democracy. In order to avoid this objection, I argue for conceiving secularism in a nonmoralized way. According to my view, secularism refers solely to the institutional arrangements that a state can put in place in order to address conflicts with organized religion(s) that might emerge at the moment of advancing its ideological political project (e.g., liberalism, republicanism). Through this interpretation, it is possible to conceptualize expressions of secularism that are either not liberal (i.e., republican) or not motivated by the acknowledgment of new forms of pluralism as being the prime challenge a state faces for advancing its political project (i.e., anticlerical). As the redundancy objection shows, this is a possibility that moralized accounts of secularism preclude.